Antibiotic Susceptibility Patterns of MRSA Isolated From Healthy Individuals In Nilai, Negeri Sembilan Malaysia - Ooi, Hooi Yi (2017)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most antibiotic-resistant pathogens and is present worldwide, causing significant health problems and increase in mortality and morbidity. MRSA have acquired resistance to different classes of antibiotics, making MRSA infections difficult to treat. Hence, it is important to carry out in vitro antibiotic susceptibility testing to obtain the antibiotic sensitivity patterns of MRSA thus utilizing the results as a guidance for antibiotic therapy of MRSA infections and formulating antibiotic policy as well as appropriate control measures. This study was aimed at determining the antibiotic susceptibility patterns of MRSA isolated from samples that were collected from healthy individuals in Nilai, Negeri Sembilan. Culture samples were inoculated on the nutrient agar plates to obtain single colonies, followed by sub-culturing and series of confirmatory tests such as Gram staining, catalase test, Mannitol Salt Agar, oxacillin disk-diffusion test and Brilliance MRSA 2 agar to obtain pure MRSA isolates. A total of 20 MRSA strains from 23 pure culture isolates were obtained and subjected to antibiotic susceptibility test on Mueller Hinton agar using Kirby-Bauer disk diffusion technique. All 20 MRSA isolates (100%) showed resistance towards oxacillin, penicillin G and vancomycin; 85% of them were resistant to erythromycin; 80% showed resistance to clindamycin, teicoplanin and linezolid; 65% of them were resistant to nalidixic acid while only 5% of them showed resistance to azithromycin and cefazolin respectively. All isolates (100%) were susceptible to ciprofloxacin. Five different antibiogram patterns were obtained from these 20 MRSA isolates with resistance towards 8 out of 11 types of antibiotics used in this study. This finding which is a surveillance control method of antibiotic resistant crisis is important as the results could provide a basis for the antibiotic therapy of MRSA infections in Malaysia.